Lesotho : Staff Report for the 2001 Article IV Consultation and the Second Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines Lesotho's 2001 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility Arrangement, and a Request for Waiver of the Performance Criterion. The economic program remains on track. Key economic indicators are performing as expected, and all quantitative performance criteria for end-September 2001 were observed. However, one structural performance criterion, making the Lesotho Revenue Authority operational, was delayed because of late parliamentary action. One benchmark-completing the 2000/01 public accounts for auditing-was not completed because of a decision to complete accounts from 1993/94 in sequence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet